Pemetaan Penelitian Bencana Dan Keamanan Wisata di Indonesia: Analisis Bibliometrik 2016-2025 - Ari Sulistyanto; Tbarani Sjahrizal (Yayasan Literasi Sains Indonesia, 2026)
Indonesia is one of the countries most vulnerable to natural disasters, making tourism safety and security a critical component of sustainable tourism development. Although research on disasters and tourism safety has continued to expand, the evolution of its intellectual structure and major research themes in Indonesia has not yet been comprehensively mapped. This study aims to analyze the development of research on disasters and tourism safety in Indonesia during the period 2016–2025. A bibliometric approach was employed. Data were collected from Google Scholar, and publications meeting the inclusion criteria were analyzed and visualized using VOSviewer to identify publication trends, citation patterns, collaboration networks, and the thematic structure of the research. The findings indicate that publications on disasters and tourism safety in Indonesia have increased consistently over the past decade. Tourism safety has emerged as one of the primary research focuses and the most frequently referenced themes. However, the keyword network remains relatively simple and exhibits limited thematic diversity, while also indicating a shift in research approaches. This study concludes that tourism safety has evolved into an essential component of sustainable tourism development in Indonesia. Future research is recommended to expand bibliographic data sources, strengthen interdisciplinary collaboration, and explore risk communication, digital transformation, and collaborative governance as key research agendas.